Incorporating Intraoperative Mechanomyography to Peripheral Nerve Decompression Surgery. Issue 4 (10th April 2023) - Guerrero, Jaime R.; Taghlabi, Khaled M.; Bhenderu, Lokeshwar S.; Cruz-Garza, Jesus G.; Javeed, Saad; Dibble, Christopher F.; Ray, Wilson Z.; Faraji, Amir H.
Abstract : BACKGROUND: Mechanomyography (MMG) is a novel intraoperative tool to detect and quantify nerve activity with high sensitivity as compared with traditional electromyographic recordings. MMG reflects the mechanical vibrations of single motor units detected through accelerometer sensors after direct motor neuron stimulation. OBJECTIVE: To determine the feasibility of applying intraoperative MMG during peripheral nerve surgery. METHODS: A total of 20 consecutive patients undergoing surgical decompression of the ulnar nerve at the cubital tunnel or common peroneal nerve at the fibular head were included in this study. Intraoperatively, the common peroneal and ulnar nerves were directly stimulated through the MMG electrode probe starting at 0.1 mA threshold and increasing by 0.1 mA increments until target muscle activity was noted. The lowest threshold current required to elicit a muscle response was recorded before decompression and after proximal and distal nerve decompression. RESULTS: Of the patients, 80% (16/20) had MMG signals detected and recorded. Four patients were unable to have MMG signal detected despite direct nerve visualization and complete neurolysis. The mean predecompression stimulus threshold was 1.59 ± 0.19 mA. After surgical decompression, improvement in the mean MMG stimulus threshold was noted (0.47 ± 0.03 mA, P = .0002). Postoperatively, all patients endorsed symptomatic improvement with no complications. CONCLUSION: MMG may provide objective guidance for the intraoperative determination of the extent of nerve decompression. Lower stimulus thresholds may represent increased sparing of axonal tissue. Future work should focus on validating normative values of MMG stimulus thresholds in various nerves and establishing clinical associations with functional outcomes. Abstract :